Karakterisasi penyebab penyakit kanker batang pada pepaya (Carica papayae L.) di Kecamatan Limau, Kabupaten Tanggamus, Lampung - AM, Shakila Larasati; Suharjo, Radix; Maryono, Tri; Masyuda, Imam; Taha, Farhan (Jurnal Proteksi Agrikultura, 2024)
This study aims to determine the pathogen characteristics of papaya stem cancer and identify alternative host plants other than papaya. The research was conducted from October 2020 to May 2021 in the Laboratory of Agricultural Biotechnology and the Laboratory of Plant Diseases, Faculty of Agriculture, University of Lampung. Four bacterial isolates suspected to be the cause of papaya stem cancer in Limau (Tang 2(1), Tang 2(2), Ptl 1(2), Ptl 2(2)) were used in this study. Bacterial characterization was determined based on the results of biochemical tests. The results showed that the bacterial isolates were gram-negative, fermentative, lecithinase-negative, soft rot-negative, and hypersensitivity-negative, and did not produce fluorescence on King's B media. All isolates were positive for the arginine dihydrolase test, except for Tang 2(2) and Ptl 1(2). All isolates showed a negative reaction in the casein test, except for Tang 2(2). All isolates were able to grow at 39 °C or 40 °C. All bacterial isolates were able to utilize mannitol, L-tartrate, and mannitol, but not ascorbic acid. The results of the host range test showed that the bacteria were able to infect and cause symptoms in eggplant, chickpeas, luffa, and long beans. A pathogenicity test was conducted on 2-month-old papaya seedlings (cv. Calina). The results showed that all four bacterial isolates from Limau caused stem cancer symptoms in the papaya seedlings.